Editorial Notes - Ab Wahid, Hariyaty (International Business Education Journal, 2025)
The International Business Education Journal (IBEJ), Volume 18, Issue 2 (2025), offers a compelling collection of research articles that illustrates the dynamic intersection of business education, entrepreneurship, customer behaviour, accounting, marketing, management, and economics. Each contribution underscores the significance of both empirical and conceptual insights in shaping policy and institutional strategies in developing nations, with a particular focus on Southeast Asian and West African countries.